2023
DOI: 10.1186/s12888-023-04575-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of stress and anxiety among female employees of hawassa industrial park in sidama regional state, Ethiopia

Abstract: Background Work-related stress and anxiety are emerging global public health problems causing serious social and economic consequences. Working women bear a heavy burden due to high social disparity, gender inequality, and an important responsibility to balance work and family life in undeveloped society. Objective To assess the prevalence and associated factors of work related stress and anxiety among female employees of Hawassa industrial park in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Post-traumatic stress for healthcare workers, particularly nurses who are twice as likely to suffer from PTSD (Pahtrol et al, 2023). In Ethiopia, nurses suffer work-related stress as women face gender inequality and economic distress (Kefelew et al, 2023). A study conducted in Turkey indicated a dire need for work environment improvement for nurses as they were anxious and complained of stress disorders (Ata et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic stress for healthcare workers, particularly nurses who are twice as likely to suffer from PTSD (Pahtrol et al, 2023). In Ethiopia, nurses suffer work-related stress as women face gender inequality and economic distress (Kefelew et al, 2023). A study conducted in Turkey indicated a dire need for work environment improvement for nurses as they were anxious and complained of stress disorders (Ata et al, 2023).…”
Section: Introductionmentioning
confidence: 99%